Bean responds to Endospor 33® at reduced dose of Nitrogen and Phosphate fertilizer in protected agriculture - Sanchez-Yañez, Juan Manuel (2014)
Bean is a legume its production requires nitrogen (N) combined as ammonium (NH4) or nitrate (NO3) and phosphates (NPF), its indiscriminate application causes soil lost productivity. An alternative solution for reducing and optimizing NPF is applying mixed inoculant which could be improved by plant growth promoting bacteria (PGPB) and mycohrrizae. The objective of this research was to analyze the response of beans to mixed inoculant Endospor 33® at 50% reduced dose of NPF. In that sense a red ferralitic soil poor in N and organic matter was used. By experimental design: 5 treatments and 6 replications. Results showed a positive bean responds achieving 100% germination at 20mg/seed with Endospor 33® at 50% NPF dose. At seedling level bean was 6.63g of total fresh weight (TFW) and 0.66g total dry weight (TDW) with the same Endospor 33® dose compared to 0.28g of TDW of bean used as relative control (RC) at 100% NPF dose. At flowering with 30 mg/plant got 1.5 g of TDW compared to 1.0g TDW of bean as CR. At physiological maturity bean with 30mg/plant had 34.83g/100 grains compared to 20.39g/grains of bean as CR. Those data supporting that Endopre 33® is an excellent choice in beans production at NPF 50% dose but not adverse effect on bean growth and yield in protected agriculture.